P028 DYSBIOSIS DRIVEN LUMINAL MALMETABOLISM INCREASES THE RISK OF C. DIFFICLILE INFECTION IN PATIENTS WITH ULCERATIVE COLITIS. (18th January 2018) - Nagao-Kitamoto, Hiroko; Kitamoto, Sho; Kamada, Nobuhiko
Abstract: Backgrounds: Clostridium difficile infection (CDI) is recognized as a major clinical complication in patients with ulcerative colitis (UC). However, the mechanism associated with increased susceptibility to C. difficile in UC patients remains poorly understood. Given the evidence that the gut microbiota plays a critical role in the prevention of CDI and that gut microbiota is perturbed in UC patients, we hypothesized that UC-associated gut dysbiosis contributes to the increased susceptibility of patients to CDI. Methods: Germ-free mice were colonized with the gut microbiotas isolated from either UC patients or healthy controls (UC/HC-microbiota (Mb) colonized humanized gnotobiotic (hGB) mice). Luminal metabolites of hGB mice were analyzed by CE-TOFMS. UC and HC hGB mice were infected with C. difficile to examine the susceptibility to CDI. Results: UC-Mb hGB mice were susceptible to C. difficile, while HC-Mb hGB mice were completely protected. Luminal metabolisms were significantly altered in UC-Mb GB mice. In particular, the level of succinate, a microbial metabolite known to aid the growth of C. difficile, was significantly increased in UC-Mb hGB mice. It was likely due to the decreased abundance of succinate consuming bacteria in UC-Mb hGB mice. An isogenic mutant C. difficile strain, which lacks the succinate utilization operon, exhibited an impaired colonization to UC-Mb hGB mice, indicating that succinate is a key metabolite that promotes the colonization of C. difficile in UC-Mb hGB mice. Furthermore, transplantation of healthy microbiotas into UC-Mb GB mice increased the succinate consuming bacteria and reduced the luminal succinate, thereby restoring the colonization resistance against C. difficile. Conclusion: UC-associated dysbiosis impairs microbial metabolic activities in the gut and increases host susceptibility to C. difficile.